Parental Knowledge, Attitudes, and Practice toward their Epileptic Children, Baghdad, Iraq 2022 - AlQaisi, Sama A.; Lami, Faris H.; Ali, Eman M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Epilepsy is one of the most common neurological disorders. People who know less about epilepsy tend to have negative ideas about the disease. KAP of parents on epilepsy is crucial, especially to children below 13, as the child in this stage mostly depends on parents to get the answers to their concerns. Still, the overprotection from their families will create insecurity and reduce their self-esteem when they grow older. Objectives: To assess the knowledge, attitude, and practice (KAP) and measure their association with sociodemographic characteristics. Methods: A cross-sectional study involved 107 parents with children who were diagnosed and received treatment for epilepsy. This study was conducted in the consultation clinics in the Children Welfare Teaching Hospital, Medical City, in Baghdad, Iraq, from January through July 2022. A questionnaire was developed and filled out through direct interviews with the participants. The questionnaire was composed of five parts. The first part included primary sociodemographic data. The second part concerns the particular child’s basic characteristics and epilepsy history. The third part concerns the parents’ knowledge about child epilepsy. The fourth part concerns parents’ attitudes toward children with epilepsy. The fifth part is concerned with the practice of parents toward child epilepsy. Results: Good knowledge, attitude, and practices were seen among 61 (57.0%), 70 (65.4%), and 90 (84.1%) parents, respectively. Good parents’ knowledge of epilepsy was significantly associated with higher education (college) and with fewer family Members (<5), respectively. In addition, a good parent’s attitude towards epilepsy was significantly associated with higher education (college). Conclusion: About half of the parents have good knowledge, two-thirds have a good attitude, and most have good practices regarding epilepsy.